Atlas of Laparoscopic and Robotic Single Site Surgery - Kaouk, Jihad H.; Stein, Robert J.; Haber, Georges-Pascal (Springer New York : Imprint: Humana Press, 2017)
This text provides a broad and current review of this field and will serve as a valuable resource for trainees, academic and community surgeons, and members of industry with an interest in LESS. Due to the novelty and complexity of these procedures, the book focuses on detailed descriptions as well as pertinent illustrations for various upper and lower tract urologic procedures. The development of novel minimally invasive and robotic technology for more comfortable performance of these demanding procedures is covered. A complete description of instrumentation, platforms, and optics developed specifically for LESS is another primary focus of this text. Finally, a description of outcomes and complications as well as comparative data defining the status of LESS in relation to other current minimally invasive techniques is offered. Atlas of Laparoscopic and Robotic Single Site Surgery provides a detailed summary of the current status of LESS that will help guide surgical decision making, encourage investigative efforts, and stimulate industry led technology development.- Resumé vydavatel
Keywords: laparoskopická chirurgie; urologie; chirurgie; laparoscopic surgery; urology; surgery; elektronické knihy; atlasy; electronic books; atlases